Pembentukan Rumah Vegetatif Tanaman Hias Sebagai Wadah Pemberdayaan Ibu Rumah Tangga Desa Sipungguk, Kabupaten Kampar, Riau - Adisti Permatasari Putri Hartoyo; Muhammad Kanzun Nafis; Nurafni Natasya; Kamilia Ulfah; Sopha Erna Ariyana; Fajar Raihan (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Pandemic Covid-19 has caused new hobbies in the community. One of them is housewives in Sipungguk Village, Salo Sub-Regency, Kampar Regenci, Riau. Their new hobby is the ornamental gardening. However, the limited income and the price of ornamental plants is increasing, so they are reconsidering in adding their collection. Based on the background, this activity aims to: 1) Train the partners (housewives) in ornamental vegetative propagation; 2) Calculate the percentage of live ornamental plants that have been propagated vegetatively; and 3) Initiate the establishment of an ornamental plant vegetative house (Ruvetas) an an business for the partners. The activity stages consisted of socialization, training and practice in making the planting media, cutting of Aglaonema and Caladium, cutting and grafting of Bugenvil, plants maintenance, as well as the ornamental plant business education. The results showed there were siginificantly knowledge improvement to the housewives, specifically in ornamental plants introduction (34%), making the planting media (45%), Aglaonema and Caladium cuttings (27%), Bugenvil cutting and grafting (45%), plants maintenance (33%), and ornamental plant business education (38%). The percentage of live ornamental plants that have been propagated vegetatively by the partners showed the high survival rate, namely 86% of Aglaonema cutting, 90% of Caladium cutting, 100% of Bugenvil cutting, as well as 67% of Bugenvil grafting. As an effort in initiating RUVETAS establishment and a business, the ornamental plants have been sold directly and thorugh digital platform in social media (Instagram dan Facebook), also in digital marketplace (Shopee). Housewives knowledge, skills, and business initiatves for ornamental plants have been significantly increased thorugh this activity.